Invited Paper: Electrophoretic Display Platform Comprising B, W, R Particles. Issue 1 (June 2014) - Wang, Ming; Lin, Craig; Du, Hui; Zang, HongMei; McCreary, Michael
Abstract The world's first mass production three‐particle electrophoretic display has been launched. E Ink SpectraTM displays utilize black, white and red engineered particles in a colorless solvent to achieve red plus black/white independent optical states without a color filter array. The three types of particles have different properties and are well controlled so they respond differently to various electric fields. The Spectra electrophoretic ink is filled and then sealed in a thin film Microcup® structure using a roll to roll process and the output imaging film can be easily cut to any shape and size and then laminated to TFT or segmented backplanes to form display modules.